Piriformospora indica confers drought tolerance on Zea mays L. through enhancement of antioxidant activity and expression of drought-related genes - Xu, Le; Wang, Aiai; Wang, Jun; Wei, Qiao; Zhang, Wenying (The Crop journal, 2017)
Drought stress is one of the most severe environmental constraints to plant growth and crop productivity. Plant growth is greatly affected by drought stress, and plants, to survive, adapt to this stress by invoking different pathways. Piriformospora indica, a root-colonizing endophytic fungus of Sebacinales, promotes plant growth and confers resistance to biotic and abiotic stresses, including drought stress, by affecting the physiological properties of the host plant. The fungus strongly colonizes the roots of maize (Zea mays L.) and promotes shoot and root growth under both normal growth conditions and drought stress. We used polyethylene glycol (PEG-6000) to mimic drought stress and found that root fresh and dry weight, leaf area, SPAD value, and leaf number were increased in P. indica-colonized plants. The antioxidative activities of catalases and superoxide dismutases were upregulated within 24h in the leaves of P. indica-colonized plants. Drought-related genes DREB2A, CBL1, ANAC072, and RD29A were upregulated in drought-stressed leaves of P. indica-colonized plants. Furthermore, after drought treatment, proline content increased, whereas accumulation of malondialdehyde (MDA), an indicator of membrane damage, decreased in P. indica-colonized maize. We conclude that P. indica-mediated plant protection against the detrimental effects of drought may result from enhanced antioxidant enzyme activity, proline accumulation, and expression of drought-related genes and lower membrane damage in maize plants.